Soft tissue coverage of a heel skin defect in a pediatric patient - Matelič, Alja (Surgery and surgical endoscopy, 2019)
A reconstruction ladder is used to decide how to treat a variety of skin defects. Often it is good to have alternative possibilities, such as a dermal matrix. This case report presents the case of a 4-year-old boy who suffered an injury to his right leg. Despite appropriate primary surgical treatment, the infection caused a skin defect with an exposed calcaneus bone. The wound was covered with a dermal matrix and later with a split-thickness skin graft. The aesthetic and functional outcomes of the treatment were satisfactory.
Keywords: kožne obloge; obloge; otroci; poškodbe; rane